Deposit insurance and market discipline - Quintero-V, Juan C. (Journal of Financial Stability, 2023)
Limited coverage is a standard feature in deposit insurance schemes. It is used to limit moral hazard, and achieves this objective by reinforcing market discipline: depositors have more incentives to monitor banks’ risk-taking if they have skin in the game. In this paper, I study market discipline and coverage levels by analyzing the relationship of funding costs and deposit growth with banks’ risk. I use a database of Colombian banks’ balance sheets and take advantage of a sudden, significant, and exogenous increase in the coverage level that occurred in April 2017. I find evidence of market discipline throughout the period of analysis and most results are consistent with it not being reduced by the change in the coverage level. The results are nuanced, however. Two variables are impacted: one in the quantity and the other in the price dimension. Furthermore, results also vary when I look at specific groups of banks separately. Market discipline is not present in big banks. Too big-to-fail perceptions seem to limit it. This is also the case for banks concentrated in fully insured deposits, where limited coverage has a less prevalent role.